Static analysis : 22nd International Symposium, SAS 2015, Saint-Malo, France, September 9-11, 2015, Proceedings /: 22nd International Symposium, SAS 2015, Saint-Malo, France, September 9-11, 2015, Proceedings. (2015) - Unknown
No abstract available